Reinterpreting Sonnet 18 by William Shakespeare through Stylistic Analysis - BANARES, ANGELICA JOYCE (International Journal of Arts, Sciences and Education, 2022)
This paper aims to examine the free Filipino translation by Gregorio V. Bituin Jr. of Sonnet 18 by William Shakespear. And since it is a text analysis, Qualitative Descriptive method was employed. The researcher used a copy of the sonnet 18 freely translated by Gregorio V. Bituin Jr. as an instrument in this study. Data gathered were chosen one of the featured Filipino translation of the Sonnet. The researcher analyzed the copy of the sonnet by analyzing each verse of the poem from the poet’s perspective. The analysis is done under the levels of Phonological, Grammatical and Lexical patterns. The various Literary Devices used in the analysis of the sonnet were also identified and linked to romanticism. This research helps to examine the structure and style of Shakespeare’s poetry through the independent translation by Gregorio V. Bituin Jr. and his themes, perspectives, and treatment of nature and his beloved. From this study, it was found that the poet uses images in his sonnet to make the readers feel and use figurative words so that it contains deep meaning. From the conclusions, the researcher suggests to the next researchers to choose the sonnet as the subject of the research because only a few choose the sonnet as the subject of their research. Keywords: Style, Stylistics, Phonological, Graphological, Lexical